The Spread of Traditional Steam Bathing as a Track Identification of Spices in Indonesia - Gaya Mentari; Yuhaswita (Universitas Airlangga, 2022)
Spices are a hot issue that is now being discussed by various groups. The Presence of spices in the archipelago became one of the pioneers for various cultural manifestations that appeared in various regions of the archipelago. One form of the presence of spices that is reflected in this cultural form is the traditional steam bath which is carried out in various regions in the archipelago. This paper tries to examine the traditional steam bath which has the potential to become an intangible cultural heritage in Indonesia. In addition to this potential, traditional steam baths can also be an indicator of the distribution of spice plants in the archipelago from the past to the present. Therefore, this study uses qualitative methods and searches for sources of information from literature studies. The result of the study shows that traditional steam bathing is a spice bath tradition that is spread across ten regions in Indonesia and is dominated by people who have a background of Malay cultural influence.